2018
DOI: 10.21037/tlcr.2018.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for small cell lung cancer

Abstract: The prognosis of limited-stage small cell lung cancer (LS-SCLC) continues to improve and is now roughly comparable to that of locally advanced non-small cell lung cancer (NSCLC). This shift, taken together with the decreased toxicities of modern radiotherapy (RT) for LS-SCLC compared with those reported in historical trials, necessitates further evaluation of whether proton beam therapy (PBT) could further reduce both acute and late toxicities for patients receiving concurrent chemoradiotherapy for LS-SCLC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…Surgical treatment has been proved to be beneficial not (8). We observed the similar results in IA-IB CSCLC patients as previous studies, which indicated the importance of surgical treatment in early stage of CSCLC.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Surgical treatment has been proved to be beneficial not (8). We observed the similar results in IA-IB CSCLC patients as previous studies, which indicated the importance of surgical treatment in early stage of CSCLC.…”
Section: Discussionsupporting
confidence: 89%
“…Moon and his colleagues used the same database to study early stage of SCLC from 1988 to 2014. They reported the CSCLC cases accounted for 6.4% of SCLC in their cohort (8). However, the proportion of CSCLC was just 2.1% in our cohort.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“… 1 SCLC tumors generally become chemoresistant after effective chemotherapy treatments, and most patients die from a recurrence of cancer or from serious complications. 2 Hence, it is important to explore the molecular mechanisms underlying SCLC progression. microR-NAs (miRNAs), a type of small noncoding RNA with a length of 19–25 nucleotides, can inhibit the expression of their target genes by binding to their 3′-UTR, resulting in mRNA degradation or posttranslational repression.…”
Section: Introductionmentioning
confidence: 99%